Equivalent concrete thickness for perforation of mild steel plates. (August 2017) - Abdel-Kader, Mohamed; Fouda, Ahmed
Abstract: Estimating experimentally the equivalent concrete thickness for perforation of mild steel plate targets subjected to hard projectiles (regardless the steel plate will be used as steel linear or not) was the aim of this study. The paper presents the experimental results on perforation of plain concrete panel targets of different thicknesses (100–600 mm) in addition to experimental results on perforation of mild steel plate targets tested under the same circumstances. Twenty-seven shots of hard projectiles perforation test on plain concrete and mild steel plates were conducted (some of these experiments have been presented before). Two formulae relating the perforation resistance of mild steel plate to an equivalent concrete thickness are proposed; one for converting a thin steel liner to an equivalent concrete thickness, and the other for replacing a steel plate target with an equivalent concrete target (and vice versa). Both formulae are influenced by the concrete strength, mass and diameter of projectile. Highlights: Twenty-seven shots of hard projectiles perforation test on plain concrete and mild steel plates Experiments on perforation of concrete and steel plates tested under the same circumstances Estimating experimentally the equivalent concrete thickness for perforation of mild steel plates Formulae relating the perforation resistance of a steel plate to an equivalent concrete thickness